Does FDI Matter for The Economic Growth of West Sub-Saharan African Countries? A Panel Vecm Approach - Nicholas, Edward (Muslim Business and Economics Review, 2024)
This study analyzes foreign direct investment (FDI) and economic growth in fifteen West Sub-Saharan African countries’ relationship from 1990 to 2020, with secondary panel data from the World Bank (2022), at the expense of both interest rate and exchange rate effect. The main model used is Panel VECM. The results shows that FDI helps enhance economic growth in the long run, as the estimate in the long-run indicates an increase of -121.16, which can be interpreted inversely with a 1% level of significance, with t-statistics at -14.94, despite FDI’s negative impact in the short run with an estimate of -3.5 with a level of significance of -2.16. Likewise, the effect of interest rate with t-statistics of -0.1 for economic growth and 0.1 for FDI and exchange rate with t-statistics of -0.43 for economic growth and -0.12 for FDI. Thus, both parameters are deemed insignificant. Therefore, policymakers should adopt policies that will support FDI for the long term to enhance economic growth, and reduce interests rate and exchange rates by establishing usage of a single currency or flexible exchange rates. This study aims to help policymakers and analysts determine the advantages of monitoring changes in macroeconomic fundamentals and economic growth for attracting FDI. The results of the study have significant policy repercussions, particularly for fiscal and monetary policy, particularly to resolve problems of slow economic growth to a low proportion of appropriate FDI in West Sub-Saharan African countries and other developing countries.